2013
DOI: 10.1371/journal.pone.0070689
|View full text |Cite
|
Sign up to set email alerts
|

B7-H3 is Overexpressed in Patients Suffering Osteosarcoma and Associated with Tumor Aggressiveness and Metastasis

Abstract: B7-H3 is a member of the B7-family of co-stimulatory molecules, which has been shown to be broadly expressed in various tumor tissues, and which plays an important role in adaptive immune responses. The role of B7-H3 in osteosarcoma, however, remains unknown. In this study we used immunohistochemistry to analyze B7-H3 expression in 61 primary osteosarcoma tissues with case-matched adjacent normal tissues, and 37 osteochondroma and 20 bone fibrous dysplasia tissues. B7-H3 expression was expressed in 91.8% (56/6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
133
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(143 citation statements)
references
References 40 publications
7
133
0
3
Order By: Relevance
“…Several studies reported that B7-H3 promoted tumor invasion and metastasis in cutaneous melanoma (30), osteosarcoma (25), and non-small cell lung cancer (31). In this study, we found that both the cell migratory and invasive potential in the B7-H3 knockdown groups of Maver and Z138 cells was reduced compared to the NC groups.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Several studies reported that B7-H3 promoted tumor invasion and metastasis in cutaneous melanoma (30), osteosarcoma (25), and non-small cell lung cancer (31). In this study, we found that both the cell migratory and invasive potential in the B7-H3 knockdown groups of Maver and Z138 cells was reduced compared to the NC groups.…”
Section: Discussionsupporting
confidence: 51%
“…Tekle et al demonstrated that the B7-H3 silencing reduced metastatic capacity of MDA-MB-435 melanoma cells and significantly increased the survival of nude mice (20). Other studies also reported that B7-H3 was important in regulating the adhesive, migratory, and invasive capacity in breast cancer (21), glioblastoma (22), pancreatic cancer (23), prostate cancer (24) and osteosarcoma (25). Liu et al discovered that silencing of B7-H3 sensitized the breast cancer cell lines to paclitaxel by abrogating Jak2/Stat3 phosphorylation (26).…”
Section: Introductionmentioning
confidence: 99%
“…In more recent studies of patients with prostate cancer, tumor B7-H3 expression was strongly correlated with disease spread at time of surgery, increased risk of clinical cancer recurrence, and cancer-specific death (20,21). Moreover, tumor B7-H3 expression was correlated with poor patient survival in clear cell renal cell carcinoma, urothelial cell carcinoma (22,23), ovarian cancer (24), glioblastoma (25), osteosarcoma (26), pancreatic cancer (27), and neuroblastoma (28). A few earlier reports have also implicated a positive immunologic function of B7-H3; e.g.…”
mentioning
confidence: 98%
“…Based on the mouse B7-H3 crystal structure, the FG loop of the IgV domain was identified to play a critical role in its T cell inhibitory function (33). B7-H3 is widely expressed among solid tumors, including prostate (20,21), renal cell carcinoma, urothelial cell carcinoma (22,23), ovarian cancer (24), glioblastoma (25), osteosarcoma (26), neuroblastoma (28), diffuse intrinsic pontine glioma (34), mesothelioma (35), and pancreatic cancer (27).…”
mentioning
confidence: 99%
“…CD276 was a tumorassociated antigen and it played a significant role in promoting migration and invasion of cancer cells [35,36]. Importantly, overexpression of CD276 was observed in various cancers including gastric cancer [37][38][39]. It suggested that downregulation of miR-940 in gastric tumor tissues might lead to overexpression of CD276 and further contribute to metastasis of gastric cancer cells.…”
Section: Discussionmentioning
confidence: 99%